Comparison of Treatment Outcomes of Typhoid Fever with Cephalosporins Vs. Fluoroquinolones in Population of Balochistan - Tariq , Abdul; Khan , Musawir; Wali Khan , Asfand Yar; Rehman , Hafiz; Shah , Syed Ahsanullah; Noorullah; Ubaidullah; Din , Muhammad Niaz; Mohsin , Muhammad; Abdul Waseh; Kakar , Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Typhoid fever remains a significant public health challenge, particularly in developing regions such as Balochistan, Pakistan. Rising antibiotic resistance, especially to fluoroquinolones, complicates treatment. This study aims to compare the treatment outcomes of cephalosporins and fluoroquinolones in managing typhoid fever in the population of Balochistan. Methods: This qualitative comparative case study was conducted in tertiary care hospitals in Quetta, Balochistan. A total of 80 patients diagnosed with typhoid fever were purposively sampled, with 40 treated with cephalosporins and 40 with fluoroquinolones. Data were collected through semi-structured interviews, medical and record reviews. Thematic analysis was performed to assess treatment efficacy, symptom resolution, fever duration, and complication rates. Results: Cephalosporins resulted in complete symptom resolution in 87.5% of cases compared to 75% for fluoroquinolones. Fever reduction occurred within 5 days in 75% of cephalosporin-treated patients versus 62.5% in the fluoroquinolone group. Complication rates were lower in the cephalosporin group (7.5%) compared to the fluoroquinolone group (17.5%), with fewer instances of gastrointestinal issues and relapse. Patient satisfaction was higher with cephalosporins (80%) than fluoroquinolones (70%). Conclusion: Cephalosporins proved more effective in treating typhoid fever in Balochistan, with higher symptom resolution rates, quicker fever reduction, and lower complication rates. These findings suggest that cephalosporins may be a more reliable treatment option in areas with rising fluoroquinolone resistance, providing better patient outcomes and satisfaction.